Hexagones sans centre, centres sans hexagone - Anne Radeff (Cybergeo, 2012)
The triangulo-hexagonal system of Walter Christaller (Die zentralen Orte, 1933) was the subject of sharp debates among German speaking geographers from 1933 until our days. In spite of the fact that several of them denounce the mathematical errors of Walter Christaller, his unrealistic assumptions, the non-adequacy of his model to reality or his heavy totalitarian past, one sees the hexagons appear, disappear, then reappear, like an obsession or an ideal image which haunts geographers’ thought. Even when this figure disappears, the fundamental ideas of the Christallerian system remain, all founded on the concept of “center”. Why have so many authors, coming from different scientific horizons (geography or spatial planning), political (partisans of totalitarian or democratic ideals) or national (Estonia, Germany, Austria, Switzerland), defended a system condemned since its beginnings?Some among these geographers call however with a change of paradigm since the end of the 20th century. New concepts appear, sometimes even in authors still fascinated by the hexagon, which contradict partially or completely the Christallerian system: “concentrated decentralization”, “decentral concentration”, “deconcentration” or “polycentric structure” of the urban system. All these concepts however remain close to that of centrality. In reality, all the places are at the same time central and decentral, both being indissociably dependant.